Uso, disponiblidade e conservação de recursos vegetais no entorno do Parque Nacional de Sete Cidades, Piauí, Brasil - Brasileiro, Derly Pereira (2022)
This project aims to test the Hypothesis of Ecological Appearance in the Cushion Zone of the Sete Cidades National Park (PARNA) in Piauí, Brazil, seeking to understand the relationship between knowledge, use and conservation of local wood resources in a region with an environmental protection area. It will seek to inventory the plant species used by a rural community around the PARNA, identify local use categories and verify the existence of a relationship between phytosociological variables and the relative importance of useful species in the surroundings of the Conservation Unit (UC). To answer the hypothesis of the ecological appearance will be realized interviews with the residents of rural communities and a phytosociological inventory in the areas of local vegetation. The data of the interviews will be evaluated using value of use (VU) and those of the vegetation through the program fitopac. It is hoped to obtain results that can contribute to characterize patterns of use of the available resources in the region of the Sete Cidades National Park (PARNA), giving conditions to eventual studies of formulation of management and conservation plan in said Conservation Unit. These should seek support from local communities, meeting the needs of preservation of the native Caatinga and Cerrado species, as well as providing alternatives to meet the needs of these communities.